Salt Effect on the Cloud Point Phenomenon of Amphiphilic Drug-Hydroxypropylmethyl Cellulose System - Mohd. Sajid Ali; Dileep Kumar; Hamad A. Al-Lohedan (Journal of Chemistry)
Effect of two amphiphilic drugs (tricyclic antidepressant, nortriptyline hydrochloride (NORT), and nonsteroidal anti-inflammatory drug, sodium salt of ibuprofen (IBF)) on the cloud point of biopolymer hydroxypropylmethyl cellulose (HPMC) was studied. Effect of NaCl was also seen on the CP of HPMC-drug system. CP of HPMC increases uniformly on increasing the (drug). Both drugs, though one being anionic (IBF) and other cationic (NORT), affect the CP in almost the same manner but with different extent implying the role of hydrophobicity in the interaction between drug and polymer. Salt affects the CP of the drug in a dramatic way as low concentration of salt was only able to increase the value of the CP, though not affecting the pattern. However, in presence of high concentration of salts, minimum was observed on CP versus (drug) plots. Various thermodynamic parameters were evaluated and discussed on the basis of the observed results.